Willingness to Pay for a Contributory Social Health Insurance Scheme: A Survey of Rural Residents in Akwa Ibom State, Nigeria - Akwaowo, Christie Divine; Umoh, Idongesit; Motilewa, Olugbemi; Akpan, Bassey; Umoh, Edidiong; Frank, Edidiong; Nna, Emmanuel; Okeke, Uchenna; Onwujekwe, Obinna E. (Frontiers in Public Health, 2021)
Background: Health insurance is seen as a pathway to achieving Universal health coverage in low- and middle-income countries. The Nigeria Government has mandated states to set up social health insurance as a mechanism to offer financial protection to her citizens. However, the design of these schemes has been left to individual states. In preparation for the set-up of a contributory social health insurance scheme in Akwa Ibom State, Nigeria. This study assesses the willingness-to-pay for a social health insurance among rural residents in the state. Methods: The study was conducted in three local government areas in Akwa Ibom State, South south Nigeria. It was a cross-sectional study with multi-stage data collection using a demand questionnaire. Interviews were conducted with 286 household heads who were bread winners. Contingent valuation using iterative bidding with double bounded dichotomous technique was used to elicit the WTP for health insurance. Multiple regression using least square method was used to create a model for predicting WTP. Findings: About 82% of the household heads were willing to pay insurance premiums for their households. The median WTP for insurance premium was 11,142 Naira (29), 95% CI: 9,599–12,684 Naira (25–33) per annum. The respondents were predominantly middle-aged (46.8%), Ibibio men (71.7%) with an average household size of five persons and bread winners who had secondary education (43.0%) and were mainly pentecostals (51.5%). The mean age of respondents was 46.4 ± 14.5 yrs. The two significant predictors of WTP for insurance premium amongst these rural residents were income of breadwinner (accounts for 79%) and size of household (2%). The regression coefficients for predicting WTP for insurance premium are intercept of 2,419, a slope of 0.1763 for Bread winner income and a slope of 741.5 household size, all values in Naira and kobo. Conclusion: Majority of rural residents in Akwa Ibom State were willing to pay for social health insurance. The amount they were willing to pay was significantly determined by the income of the breadwinner of the household and the size of the family. These findings are relevant to designing a contributory social health insurance scheme that is affordable and sustainable in order to ensure universal health coverage for the citizens.